2011
DOI: 10.1038/jhh.2011.106
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the prevalence of metabolic syndrome in 50-year-old Swedish men and women with hypertension born in 1953

Abstract: To investigate potential gender differences in the role of hypertension as a risk factor for metabolic syndrome (MetS) we used a random population sample of 50-year-old men (n ¼ 595) and women (n ¼ 667; all born in 1953) who were examined in 2003 --2004. Systolic (SBP) and diastolic (DBP) blood pressure values were dichotomized at X140 mm Hg and X90 mm Hg, respectively. MetS was defined using NCEP (National Cholesterol Education Programme) and IDF (International Diabetes Federation) criteria. MetS was more pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 26 publications
1
10
2
Order By: Relevance
“…The gender division in the current study is about one-third males and two-thirds females. In recent Finnish and Swedish population-based studies, the MetS prevalence was somewhat higher in men than women (9, 70). For better representativeness of our study population, a higher ratio of men would have been preferable.…”
Section: Discussionmentioning
confidence: 95%
“…The gender division in the current study is about one-third males and two-thirds females. In recent Finnish and Swedish population-based studies, the MetS prevalence was somewhat higher in men than women (9, 70). For better representativeness of our study population, a higher ratio of men would have been preferable.…”
Section: Discussionmentioning
confidence: 95%
“…These findings were very similar to present study. In a Swedish study, high BP was the most common component in both sexes, followed by high waist circumference among women and changes in TG levels among men [53]. In China, the prevalence of individual components of MS was in order: high BP, TG, plasma glucose, central obesity and HDL-c in men and high BP, central obesity, TG, HDL-c and plasma glucose in women [54].…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, similar to the general population and that observed with SSPG, nonwhite race (predominantly African Americans and Latinos) was associated with metabolic syndrome in this HCV cohort . With respect to gender, studies have shown that in the general population, men have earlier onset and increased rates of metabolic syndrome than women , a difference that decreases sharply after women reach menopause . Moreover, a recent study of the Third National Health and Nutrition Survey in the United States showed that abdominal obesity was the dominant component of metabolic syndrome in women, whereas risk factor combinations were more variable in men .…”
Section: Discussionmentioning
confidence: 99%